Recombinant salmonella typhi ty21a as vaccine candidate against tuberculosis - Badrul Syam, Mat Zainuddin (2008)
A recombinant Salmonella Typhi Ty21 a vaccine was developed where the candidate [rSTvaciii(M2)] displaying a multi-epitopes mycobacterial antigen called the Vaciii(M2) (containing ubiquitin and 4 immunogenic mycobacterial epitopes of ESAT-6, PhoSI, Hsp 16.3, and MTB 8.4 genes) on the surface of Salmonella Typhi Ty21a (Ty2la) using PgsA protein as a carrier. The expression of Vaciii(M2) protein on the surface of Ty21 a was verified by Western blot. A DNA vaccine was constructed namely as pVaxVaclll, encoding the Vaclll gene. Immunization in BALB/c mice with pVaxVaclll and rSTvaciii(M2) either as homologous or heterologous vaccination, induced strong Th 1-type responses based on high levels of in vitro IFN-y but low levels of IL-4 secretion. However, the heterologous primeboost vaccination using pVaxVaclll followed by rSTvaciii(M2) induced lower IFNy production compared to homologous rSTvaciii(M2) or pVaxVaclll vaccination. Since the protective immunity against tuberculosis required Th 1-type response, these rSTvaclii(M2) and pVaxVaclll have potential as effective vaccine candidates against tuberculosis.